ANALISIS RISIKO KERJA PADA PT SINAR SEMESTA DENGAN MENGGUNAKAN METODE JOB SAFETY ANALYSIS (JSA) - Muljoko, Muljoko; Apsari, Ayudyah Eka (Yayasan Education and Social Center, 2025)
PT Sinar Semesta is a company operating in the field of metal casting and machining. In its daily production activities, workers frequently come into contact with hazardous materials that pose potential risks such as fire, workplace accidents, and environmental pollution. Therefore, the implementation of the Job Safety Analysis (JSA) method becomes a crucial step in identifying potential hazards and formulating appropriate preventive measures. JSA serves as a tool to identify risks present in the work environment and as a reference for determining suitable control measures to minimize the likelihood of accidents. Based on the hazard identification results, 13 work activities were found to fall into the high-risk category. Among these, the induction and casting/molding processes were classified as having the highest risk levels, with a strong potential to trigger workplace accidents if not properly managed. From this analysis, it can be concluded that the application of JSA plays a significant role in reducing accident risks, particularly in metal casting operations. To enhance the effectiveness of risk prevention, the company must prioritize risk control strategies—such as requiring all workers to use Personal Protective Equipment (PPE). Furthermore, it is essential to strengthen the supervision of safety procedure implementation and ensure that adequate PPE facilities are available at every stage of the production process. These efforts aim to create a safer work environment while supporting efficient and risk-free production continuity.